Exploring the Relationship of Perivascular Adipose Tissue Inflammation and the Development of Vascular Pathologies - Rami, Afifah Zahirah Abd; Hamid, Adila A.; Anuar, Nur Najmi Mohamad; Aminuddin, Amilia; Ugusman, Azizah (Mediators of Inflammation, 2022)
Initially thought to only provide mechanical support for the underlying blood vessels, perivascular adipose tissue (PVAT) has now emerged as a regulator of vascular function. A healthy PVAT exerts anticontractile and anti-inflammatory actions on the underlying vasculature via the release of adipocytokines such as adiponectin, nitric oxide, and omentin. However, dysfunctional PVAT produces more proinflammatory adipocytokines such as leptin, resistin, interleukin- (IL-) 6, IL-1β, and tumor necrosis factor-alpha, thus inducing an inflammatory response that contributes to the pathogenesis of vascular diseases. In this review, current knowledge on the role of PVAT inflammation in the development of vascular pathologies such as atherosclerosis and hypertension was discussed.